1981
DOI: 10.1107/s002188988100856x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of malononitrile. Crystallographic characterization of theLFphase transition

Abstract: The L-F phase transition of malononitrile, CH2(CN)2, has been characterized by powder X-ray diffraction analysis. The powder data of L and F phases are given. Crystallographic results are consistent with spectroscopic and calorimetric ones which indicate that this transition is of first order and corresponds to a reconstructive mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…We do not discuss the δ-phase here, but as part of the present study we obtained a pure phase and showed that it has a tetragonal unit cell with lattice parameters a = 7.2842(2) Å, c = 14.430(4) Å. This is largely consistent with the previously published x-ray powder diffraction study [10] and the author's previously unpublished x-ray measurements [9]. What is important here is that the β and α-phase structures are metastable for temperatures below 260 K, but only at temperatures close to 260 K is there a chance that the transformation to the δ-phase can be driven by annealing.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…We do not discuss the δ-phase here, but as part of the present study we obtained a pure phase and showed that it has a tetragonal unit cell with lattice parameters a = 7.2842(2) Å, c = 14.430(4) Å. This is largely consistent with the previously published x-ray powder diffraction study [10] and the author's previously unpublished x-ray measurements [9]. What is important here is that the β and α-phase structures are metastable for temperatures below 260 K, but only at temperatures close to 260 K is there a chance that the transformation to the δ-phase can be driven by annealing.…”
Section: Introductionsupporting
confidence: 91%
“…We note here that there exists a fourth crystalline phase of malononitrile, which is stable below 260 K and which we denote here as the δ-phase 3 . This was revealed by the NQR measurements [3,4], through the observation of a large latent heat in the heat capacity measurements performed with sufficient annealing time [5], from x-ray powder diffraction measurements [9,10], and in some of the spectroscopy studies [11]. All these reports suggest that the transformation to the δ-phase is sufficiently slow that the β-phase can be cooled without transforming to the δ-phase, as found in this study, although holding one sample at 240 K on cooling in this work did result in the transformation.…”
Section: Introductionmentioning
confidence: 98%
“…The two calculated lattice parameters agree with the experimental data with an underestimate of 2.6% in both cases. We remark that the experimental data are not for low temperatures so there will be an effect of thermal expansion, which could reasonably account for some of the discrepancy 8 . We also compare the experimental (5 K) and DFT-calculated crystal structures of the α phase in table 3.…”
Section: Crystal Structuresmentioning
confidence: 86%
“…There have been two previous, but inconclusive, x-ray powder diffraction studies of δ-malononitrile [8,9]. These showed drastic changes in the diffraction patterns, consistent with a reconstructive phase transitions.…”
Section: Introductionmentioning
confidence: 92%